Pluto and Charon ice worlds on the ragged edge of the solar system - Stern, Alan 1957- (John Wiley & Sons, 1998)
"Pluto and Charon explores the remote, icebound reaches of our planetary system in an interwoven tale of exotic Pluto, its unusual satellite companion Charon, and the dynamic, high-technology world of twentieth-century astronomy. Astronomers Alan Stern and Jacqueline Mitton recount a story of planetary astronomy at its frontier. The book begins with a description of the dramatic discovery of Pluto by Clyde Tombaugh in 1930, and continues through to the latest images of Pluto taken by the Hubble Space Telescope, and the effort to build Pluto Express, a NASA reconnaissance mission to the only planet not yet visited by spacecraft." "Three themes thread this new book. The first concerns the advances made possible by dramatic improvements in ground-based astronomical instrumentation. Second is the revolution in scientific perspective wrought by spacecraft visits to the planets. Stern and Mitton's third theme concerns the cultural revolution that has taken place as humans, born and bred on Earth, have come to know exotic and far distant worlds as real places."--Jacket.